Ethical Design for Edtech Platforms – An Analysis of Google Classroom via a Code of Design Practices - Pereira, Steffano; Rebelo, Maria Eduarda; Valença, George (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: The widespread adoption of EdTech platforms in schools exposes children to significant risks that confict with their rights under the UN Convention on the Rights of the Child (UNCRC). These risks include the opaque collection and processing of personal data for non-educational purposes, the use of this data for commercial profiling, and a lack of user control, which undermines their rights to privacy and protection from economic exploitation. Objective: This paper aims to address these risks by developing a practical ethical design guide. The guide is intended to empower educational institutions to assess and select EdTech platforms that are designed to proactively protect children’s rights. Methodology or Steps: The guide was developed through a multi-phase process: a review of academic and gray literature to identify best practices, systematic categorization of these practices into ten key areas, and alignment with legal frameworks like Brazil’s General Data Protection Law (LGPD) and CONANDA Resolution N° 245. Results: The primary result is an ethical design guide composed of 12 actionable practices for evaluating EdTech platforms. The guide’s utility is demonstrated through a critical analysis of Google Classroom, highlighting how the framework can identify specifc data protection and ethical shortcomings in widely used educational software, thereby providing a tangible tool for fostering safer digital learning environments.